The Role of ICT to change misconceptions of some astronomy concepts in children of primary school - Bonito, Tatiana (2020)
This study was designed to investigate whether the use of Information and Communication Technologies (ICT) would be fruitful to change several misconceptions of students about astronomy (the solar system,stars, etc.). It was developed with a group of 23 children, aged between eight and nine years old, who attended the 3rdgrade of primary education in a school in Lisbon, Portugal. This research can be classified as an action-research project based on a quasi-experimental study in the context of teaching practice leading to a master ́s degree qualifying the students to be teachers in the first six years of schooling. The research was developed in several stages, being initiated with the application of a questionnaire to identify misconceptions about astronomy. The result of this application confirmed that these misconceptions were similar to those already identified by other studies with children of the same age. Subsequently, ICT were used to design activities to promote conceptual change in order to provoke cognitive conflicts in the children about their own ideas when compared with scientific ones. After this intervention, the same questionnaire was applied in two different moments in order to evaluate possible changes. The first application was at the end of the school year, right after the above mentioned treatment; the second application took place at the end of September, in the following school year, after the summer school holidays. In both applications, a marked decrease of the misconceptions held by the children was revealed, which indicates that the use of ICT can be a relevant tool to promote a persistent conceptual change.